An examination of Talal Asad’s anthropological thought on the Islamic community of Sasak Lombok - Sari, Ramadhanita Mustika; Rodiah, Ita; Fauzi, Ahmad; Jaya Bahari, Lalu Pradipta (Indonesian Journal of Islam and Muslim Societies, 2024)
The island of Lombok is inhabited by the Sasak tribe with the majority of the people being Muslim. This island is located in the small Sunda range in the central region of Indonesia. The Sasak tribe as the original inhabitants of the island of Lombok, which is also nicknamed the island of a thousand mosques, has a variety of unique religious traditions and rituals that we can only find on the island of Lombok. so many traditions in Lombok itself are still closely related to Islam. As well as the maulidan tradition, Lebaran ketupat, and several other traditions. Discussions related to Islamic tradition have been studied by many figures in the world, one of which is Talal Asad. It should also be noted that Talal Asad has criticized the textualization of social life, his work has shifted analysis through behavioral interpretation and towards an investigation into the relationship of practice with what he calls "discursive tradition." Asad introduced this concept in his intervention into Islamic anthropology but also linked it to several fields (anthropology, religious studies, postcolonial studies, critical theory) concerned with ethics and religion in modernity. Through this article, the author would like to invite readers to jointly understand the context of Islamic anthropology based on customs, traditions, and the writings of figures such as Talal Asad. This article is expected to be able to provide education to the public regarding Islam on the island of Lombok, then the history of Islam on the island of Lombok, customs, traditions, and its review based on Talal Asad’s anthropology.